Kualitas diet, kurang energi kronis (KEK), dan anemia pada pengantin wanita di Kabupaten Semarang - Dieny, Fillah Fithra; Jauharany, Firdananda Fikri; Fitranti, Deny Yudi; Tsani, A Fahmy Arif; Rahadiyanti, Ayu; Wijayanti, Hartanti Sandi; Kurniawati, Dewi Marfu’ah (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2019)
Introduction: Pre-conception women are potential mothers or vulnerable groups who need special attention. The less of nutrients Intake than necessary can lead to nutritional problems such as Chronic Energy Deficiencyand nutritional anemia that have an impact on the next phase of life such as the risk of giving birth to babies with low birth weight (LBW), babies stunting, and growth disruption and development of the fetus / baby during pregnancy or after that. Objective: To analyze the relationship between diet quality, chronic energy malnutrition status with anemia in the bride.Methods: A cross-sectional study with 70 subjects who were brides aged 16-30 years. Selection of subjects with consecutive sampling method. Dietary quality data was measured through the Semi Quantitative Food Frequency Questionnaire (SQ-FFQ) and Diet Quality Index - International (DQI-I) forms, SEZ status assessed from body mass index (BMI) and upper arm circumference (LiLA). Anemia status was measured from hemoglobin levels, MCV, MCH, and MCHC. To examine the relationship between diet quality, chronic energy malnutrition, and anemia using a linear regression test.Results: The subject aged 16-30 years, and 41.4% are still <20 years old. A total of 10 subjects (14.3%) belonged to Chronic Energy Deficiency. Haemoglobin level measurements showed there were 8 subjects (11.4%) who had low Hb levels, and 4 of them had anemia with microcytic hypychromic type which was characterized by low MCV, MCH and MCHC values. Based on the calculation of intake was known that 55 subjects (78.6%) had a low quality diet. This study showed no relationship between diet quality and anemia, but the sub-components of diet quality were adequacy of protein intake (p = 0.007), iron intake (p = 0.009) and upper arm circumference (p = 0.018) indicating a significant relationship with anemia (hemoglobin level) in the bride. Conclusion: the less protein and iron intake and lower upper arm circumference associated with a decrease in the bride's hemoglobin level